Analisis Budaya Organisasi Dalam Meningkatkan Produktivitas Kerja Pada Perusahaan Gamis Geulis (GG) - Mardiana, Ginan; Nadari Aristi, Vesti (CV. ULIL ALBAB CORP, 2025)
This study discusses how organizational culture can enhance work productivity at the Gamis Geulis (GG), a garment manufacturing business in Bandung. Using a qualitative approach through interview, observations, and documentation study. The research found that supportive work culture such as innovation spirit, attention a quality, and concern for employees plays a significant role in fostering loyalty and work motivation. Despite challenges such as declining sales and high absenteeism, employees remain productive due to a comfortable work environment and a strong sense of belonging to the company. Organizational culture is proven to be a crucial factor in maintaining performance and business sustainability.